Nickel‐Catalyzed Asymmetric Reductive Diarylation of Vinylarenes. Issue 10 (11th February 2019) - Anthony, David; Lin, Qiao; Baudet, Judith; Diao, Tianning
Abstract: A nickel‐catalyzed asymmetric diarylation reaction of vinylarenes enables the preparation of chiral α, α, β‐triarylated ethane scaffolds, which exist in a number of biologically active molecules. The use of reducing conditions with aryl bromides as coupling partners obviates the need for stoichiometric organometallic reagents and tolerates a broad range of functional groups. The application of an N ‐oxyl radical as a ligand to a nickel catalyst represents a novel approach to facilitate nickel‐catalyzed cross‐coupling reactions. Abstract : Under reducing conditions : A nickel‐catalyzed asymmetric diarylation reaction of vinylarenes enables the preparation of chiral α, α, β‐triarylated ethane scaffolds. The use of reducing conditions with aryl bromides as coupling partners obviates the need for stoichiometric organometallic reagents, and tolerates a broad range of functional groups.